Innovaciones contractuales: el Memorando de Entendimiento - López Fung, Jorge (Pontificia Universidad Católica del Perú, 2016)
This article addresses the most relevant aspects of Memorandum of Understanding, one of the most important contractual figures of our times. Through the article, the author explains this figure according to doctrinaire and jurisprudential pronouncements and determines its legal nature and the treatment the Peruvian legal system should grant to it.

El presente artículo aborda los aspectos más relevantes del Memorando de Entendimiento o Memorandum of Understanding, una de las figuras contractuales más importantes de nuestros tiempos. A lo largo del artículo, el autor explica esta figura a la luz de pronunciamientos doctrinarios y jurisprudenciales y, asimismo, determina su naturaleza jurídica y el tratamiento que el ordenamiento jurídico peruano debe otorgarle.
Contractual innovations: Memorandum of Understanding
Keywords: Memorandum Of Understanding; Option Contract; Preliminary Agreement; Pre-Contractual Liability; Contractual Liability; Memorando de Entendimiento; Contrato de Opción; Contrato Preparatorio; Responsabilidad Precontractual; Responsabilidad Contractual; https://purl.org/pe-repo/ocde/ford#5.05.00